Synthesis and Spectral Analysis of Some 4-Substituted-5,7-diarylpyridino[3,4-d]-1,2,3-selenadiazoles - Winfred Jebaraj, J.; Gopalakrishnan, M.; Baskar, G. (Asian Journal of Chemistry, 2010)
Several novel 5,7-diarylpyridino[3,4-d]-1,2,3-selenadiazoles (1-6) are prepared from their respective semicarbazones of 2,6-diarylpiperidin-4-ones. The products are analyzed by IR, 1H, 13C NMR studies and C, H, N analysis by comparing the parent selenadiazole (1) which is prepared from the semicarbazone of 2,6-diphenylpiperidin-4-one. Similarly a set of 5,7-diaryl-4-methylpyridino[3,4-d]-1,2,3-selenadiazoles (7-13), 5,7-diaryl-4-ethylpyridino[3,4-d]-1,2,3-selenadiazoles (14-19) and 5,7-diaryl-4-isopropylpyridino[3,4-d]- 1,2,3-selenadiazole (20-25) are synthesized and characterized.